2023
DOI: 10.3390/nu15194123
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mediterranean Diet Adherence with Sociodemographic, Anthropometric, and Lifestyle Factors during the COVID-19 Pandemic: A Cross-Sectional Study in Greece

Eleni Pavlidou,
Sousana K. Papadopoulou,
Maria Mentzelou
et al.

Abstract: Background: The COVID-19 pandemic has negatively affected several aspects of people’s lifestyle worldwide. Healthy dietary patterns and their bioactive components may improve or even co-treat the negative impacts of the COVID-19 pandemic in several aspects of people’s lifestyle and mental health in daily life. The aim of this survey is to evaluate the potential effect of Mediterranean diet (MD) adherence against COVID-19-induced complications. Methods: This is a cross-sectional survey performed on 3721 adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Another disadvantage of our survey is related to the fact that in the last months of our study (April 2020), the COVID-19 pandemic spread to our country, which could result in unfavorable disruptions of daily living habits by having harmful impacts on various aspects of human well-being globally [109]. This reinforces the strong demand to perform future studies to examine whether healthy dietary patterns such as MD adherence could attenuate or even co-treat the deleterious effects of the COVID-19 pandemic in diverse aspects of people's daily life, as well as whether the COVID-19 pandemic may negatively affect the socio-demographic, anthropometry, and lifestyle characteristics in the daily life of the general population as well as of pregnant women [110].…”
Section: Discussionmentioning
confidence: 96%
“…Another disadvantage of our survey is related to the fact that in the last months of our study (April 2020), the COVID-19 pandemic spread to our country, which could result in unfavorable disruptions of daily living habits by having harmful impacts on various aspects of human well-being globally [109]. This reinforces the strong demand to perform future studies to examine whether healthy dietary patterns such as MD adherence could attenuate or even co-treat the deleterious effects of the COVID-19 pandemic in diverse aspects of people's daily life, as well as whether the COVID-19 pandemic may negatively affect the socio-demographic, anthropometry, and lifestyle characteristics in the daily life of the general population as well as of pregnant women [110].…”
Section: Discussionmentioning
confidence: 96%
“…This inverse relation persisted as robust within subgroups, as well as in sensitivity analyses [54]. A more recent cross-sectional survey including 3721 adults was performed to assess the possible relation of MD compliance with several sociodemographic, anthropometric, and lifestyle factors during the COVID-19 pandemic period [55]. The above study showed that a higher MD adherence was independently associated with a lower probability of central obesity, enhanced physical activity, higher sleep quality, improved quality of life, and lower risk of anxiety and depression throughout the COVID-19 pandemic [81].…”
Section: Sars-cov-2 and Dietary Patternsmentioning
confidence: 99%
“…The quarterly meetings and nutritional interventions were based on nutritional evaluations (anthropometric, biochemical, clinical, and dietary analyses) and quantitative and qualitative nutritional strategies, through the elaboration of a personalized food plan, based on the guidelines postulated in the following references: Dietary Guidelines for the Brazilian Population-Ministry of Health/Brazil [25]; International guidelines from the American Diabetes Association 2023 [2,[11][12][13][14][15][16][17], the European Society of Cardiology 2023 [3], and the International Diabetes Federation 2021 [1]; the National guidelines from the Brazilian Diabetes Society (SBD) 2023 [23] and the Brazilian Society of Cardiology 2021 [12]; the Mediterranean Diet [28][29][30][31][32][33][34][35][57][58][59][60]; the Diet Approach to Stop Hypertension-DASH [37][38][39][40][61][62][63]; the Lifestyle Interventions in T2D-"Look AHEAD (Action for Health in Diabetes)" [18][19][20][21]; the Carbohydrate Counting Manual-SBD 2021 [24].…”
Section: Nutritional Interventionsmentioning
confidence: 99%